Trends in STEAM Research in Science Education from 2016 to 2025: A Bibliometric Analysis and Systematic Literature Review - Ahmad Aris Arifin; Agus Ramdani; A. Wahab Jufri; Satutik Rahayu (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to analyze research trends in STEAM research in science education from 2016 to 2025 by combining bibliometric analysis and a systematic literature review (SLR). Bibliometric data were retrieved from the Dimensions database using the keyword STEAM Research in Science Education. The initial search in the full data field yielded 281,366 documents; however, after restricting the search to the title and abstract fields, 1,412 publications were obtained and analyzed using VOSviewer. In addition, an SLR was conducted on 30 articles published in reputable Scopus-indexed journals. The findings reveal a significant increase in STEAM-related publications in science education, particularly after 2022, when the annual number of publications rose sharply from 127 in 2022 to 402 in 2025. This trend indicates growing academic interest in integrative, creative, and contextual learning approaches. Keyword analysis shows the dominance of general terms such as student, education, learning, system, and science, while the network visualization demonstrates strong linkages between pedagogical and applied clusters. However, the density and overlay visualizations indicate that the integration of STEAM with culture, indigenous knowledge, and ethnoscience remains peripheral. The SLR findings further show that STEAM research in science education has mainly focused on twenty-first-century skills, scientific literacy, creativity, and teacher implementation support, but remain fragmented across contexts, educational levels, and outcome variables. Therefore, this study confirms that although STEAM has developed rapidly in science education, further research is still needed to systematically integrate publication trends, thematic structures, methodological approaches, and cultural or local dimensions to strengthen future directions of STEAM research.